Natural Melanin as a Potential Biomaterial for Elimination of Heavy Metals and Bacteria from Aqueous Solution - Na, Nguyen Thi Le; Hoa, Pham Thi; Thang, Nguyen Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Development of materials for treatment of heavy metals and bacteria in aqueous solution is still on the way. Although there are many materials developed, there is limit material which could be practical applied to eliminate a wide range of heavy metal ions and bacteria in drinking water. In this study, we investigated the adsorption capacity of melanin extracted from the ink sacs of squids toward heavy metals (chromium and manganese), which normally presented at high concentrations in water sources originated  from mining, metal plating and steel making industries, as well as bacteria in aqueous solution. Our results showed that melanin could remove Cr 6+ and Mn 2+ effectively (> 97%) with the adsorption capacities to be 5.78 mg/gam and 31.8 mg/gam for Cr 6+ and Mn 2+ , respectively. More interestingly, it indicated that melanin could not only eliminate heavy metals but also effectively removed vibrio parahaemolyticus bacteria with efficiency more than 90%. The obtained results suggested that melanin, a natural material with high level of biosafety, might be a good adsorbent for removal of heavy metal ions and bacteria in aqueous solution and could be used for advantage treatment of drinking water.    Keywords: Melanin, biomaterial, water treatment, heavy metal, bacteria.